EKSISTENSI METODE JIBRIL DALAM MENINGKATKAN KEFASIHAN PELAFALAN HURUF AL-QUR'AN DI TAMAN PENDIDIKAN AL-QUR’AN AL-HIDAYAH JORONG PANINJAUAN - Satrio Abdillah; Abdul Sahib; Andiri Nirwana AN; Fahmi Dolles Marshal (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2024)
The essence of Jibril's method is talqin-taqlid (imitation), namely students imitate the teacher's reading where the teacher's position of information is as a learning resource or provider in the learning process. The aims of this method are (1) To determine the ability to read the Al-Quran of Al-Hidayah Al-Qur'an Education Park (TPA) students; (2) Knowing the application of the Gabriel method; (3) Knowing the supporting factors of the Gabriel method; (4) Knowing the factors inhibiting the Gabriel method; (5) Knowing the solution to overcome the factors inhibiting the Gabriel method. In this service, researchers use the Jibril method to teach fluency in the pronunciation of the letters of the Koran. The results obtained from using the Jibril method are that children can pronounce letters correctly according to existing regulations. Some children also feel satisfied with this method, because it makes it easier for children to recognize letters and how to read them